Ellipsis and dialogue in the early acquisition of syntax - Gómez, Fátima; López-Ornat, Susana; Gallego, Carlos; Martínez, María (Anales de Psicología / Annals of Psychology, 2013)
The transition from the one and the two-word phases to the first complete sentences was investigated. Within an emergentist scope, it was hypothesized that it would be possible to identify transitional constructions, more complex than the mere juxtaposition of two words but syntactically less mature than simple sentences. Specifically, predominance of one and two-word productions, and a marginal use of correct but non-productive sentences were predicted, together with a gradual increase of syntactic fragments, i.e., correct and non-productive ellipses, given their frequent use in the Spanish language. Hypotheses were tested through a longitudinal study of a monolingual Spanish girl, from the age of 20 to 27 months. Weekly video sessions over seven months recorded her spontaneous utterances. Those were coded together with their situational and speech contexts. The results supported and specified the hypothesis. Over time, there was an increased use of constructions we have called pre-ellipses because they mimic adult ellipses. Detailed analyses showed pre-elliptical constructions evolved from showing a local dependency on their production context, to becoming linked to the linguistic structure of the previous turn. Dialogue and its context played a fundamental role in these transitional steps into syntax.